Tinjauan Yuridis terhadap Proses Pembatalan Hibah di Pengadilan Agama: Studi Putusan Nomor 236/Pdt.G/2017/Pa.Pal. - Nasution, Zulkifli; Harahap, Mhd Yadi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Grant is one of the legal acts that is basically regulated in positive legal provisions in Indonesia, both civil law and Islamic law. However, in practice there are still some problems related to the change process, as a legal provision, of course, grants have pillars and conditions that must be met, which if there is one pillar that is not fulfilled, the contract of the grant can be canceled. In this regard, Decision Number 236/Pdt.G/2017/PA. Pal there is a request for grant cancellation made by the biological son of the grantor, so in this study the author will examine the juridical review of the grant cancellation process in religious courts as happened in Decision Number 236/Pdt.G/2017/PA. Pal to find out whether it is in accordance with applicable legal provisions. This research is qualitative research with the type of normative juridical research or legal research, literature approach or (labrary research). The results of this study show that the practice that occurred in Decision Number 236/Pdt.G/2017/PA. Pal in the case of mauhub (property granted) violates the provisions of article 210 paragraph (1) of the KHI where the maximum grant is only 1/3 of the total property of the grantor, but in this decision exceeds 1/3 part. Therefore, in the examination of the case, the Judge granted part of the plaintiff's claim, namely declaring void the grant 154/PT/IV/2009 dated April 6, 2009